Molecular detection of spotted fever group rickettsiae in hard ticks, northern China. Issue 4 (11th April 2019) - Guo, Wen‐Ping; Wang, Yi‐Han; Lu, Qizhong; Xu, Gang; Luo, Yuhang; Ni, Xuebing; Zhou, En‐Min
Abstract: Spotted fever group (SFG) rickettsiae are important causative agents of (re)emerging tick‐borne infectious diseases in humans, and ticks play a key role in their maintenance and transmission. In this study, hard ticks were collected from five sampling sites in North China in 2017 and 2018. Of them, Haemaphysalis longicornis, Rhipicephalus microplus and Dermacentor nuttalli were collected from livestock (sheep and goats) and the vegetation, Hyalomma asiaticum from sheep, goats and camels, and Hyalomma marginatum from sheep and goats. The SFG rickettsiae were identified in these ticks by amplifying the partial rrs and complete 17‐kDa genes, with an overall infection rate of 52.9%. In addition, the nearly full‐length rrs and gltA and partial ompA genes were recovered to classify the species of SFG rickettsiae further. Phylogenetic analysis revealed the presence of three human pathogenic species in Hy. asiaticum, Hy. marginatum, Ha. longicornis and De. nuttalli, including two cultured ones ( Rickettsia raoultii and Rickettsia aeschlimannii ) and one uncultured ( Candidatus R. jingxinensis). Furthermore, partial groEL gene was also obtained, and phylogenetic trees were also reconstructed to better understand the genetic relationship with known sequences in each SFG rickettsiae species detected in the current study. Notably, the R. aeschlimannii sequences described in this study were closely related to those from abroad rather than from another part of China, indicating their different origin. However, the R. raoultii and Ca . R. jingxinensis sequences presented close relationship with variants from other parts of China. In sum, our data revealed SFG rickettsiae species in northern China, highlighting the need for surveillance of their infection in local humans.